Building technology transfer within research universities an entrepreneurial approach - Allen, Thomas J. 1931-; O'Shea, Rory (Cambridge University Press, 2014)
For the past number of years, academic entrepreneurship has become one of the most widely studied topics in the entrepreneurship literature. Yet, despite all the research that has been conducted to date, there has not been a systematic attempt to analyze critically the factors which lie behind successful business spin-offs from university research. In this book, a group of academic thought-leaders in the field of technology transfer examine a number of areas critical to the promotion of start-ups on campus. Through a series of case studies, they examine current policies, structures, program initiatives and practices of fourteen international universities to develop a theory of successful academic entrepreneurship, with the aim of helping other universities to enhance the quality of their university transfer programs. This book is a valuable resource for university research administrators, technology transfer office professionals, academic entrepreneurs, incubator management officials, R&D managers, venture capitalists, researchers, policymakers, and others involved in the commercialization of intellectual property